2002
DOI: 10.3109/2000-1967-125
|View full text |Cite
|
Sign up to set email alerts
|

A case of inguinal endometriosis with difficulty in preoperative diagnosis

Abstract: An unusual case of endometriosis involving the right round ligament in a 40-yearold woman is presented. After giving birth to two children, she first noticed a tender mass in the right groin at the age of 36. It didn't change in size but pain appeared at the age of 38, disturbing her daily life. A poorly circumscribed elastic hard mass, measuring 3cm in diameter, was palpable in her right inguinal region. Magnetic resonance imaging demonstrated a 2×3 cm mass in the right inguinal canal. At operation, a mass wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The first reported case of endometriosis affecting the extraperitoneal portion of the round ligament was described by Cullen 5 in 1896, and its incidence was found to be 0.6% among women suffering from endometriosis 6 . Uzunlar et al reported 40 cases in the literature, and we were able to find a further 7 cases published in English 7–13 …”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The first reported case of endometriosis affecting the extraperitoneal portion of the round ligament was described by Cullen 5 in 1896, and its incidence was found to be 0.6% among women suffering from endometriosis 6 . Uzunlar et al reported 40 cases in the literature, and we were able to find a further 7 cases published in English 7–13 …”
Section: Discussionsupporting
confidence: 50%
“…Both showed a poorly circumscribed mass, which had the same intensity as muscle on T1W images, and higher intensities with partial low intensities on T2W images. One author described a mosaic pattern of enhancement after gadolinium injection 8 …”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][14][15][16]22 Moreover, rare cases of endometriosis have been described in uncommon sites, such as rectovaginal septum, urinary bladder, hernia sacs and umbilicus. 4,[6][7][8][9] In these cases FNC may be the only diagnostic tool in the pathologic evaluation of these lesions and provides a rapid and accurate preoperative diagnosis. Such a technique can in fact obviate the need for an invasive diagnostic procedure and resolve the differential diagnosis of palpable lesions of the abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we desired to discuss briefly the clinical implications and drawbacks of a cytopathologic diagnosis of endometriosis in view of the possible danger caused by long-term pharmacologic therapy [18][19][20][21] and of the delay that is usually associated with this diagnosis. 8,22 …”
mentioning
confidence: 99%
“…Hagiwara et al reported two cases of inguinal subcutaneous endometriosis attaching to the round ligament of the uterus. They mentioned there had been continuity between the lesion and right round ligament of the uterus, but no association with inguinal hernia [9,10].…”
Section: Endometriosis Of Inguinal Subcutaneous Tissue J Med Cases 2mentioning
confidence: 99%